2001
DOI: 10.1024/0300-9831.71.6.347
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Supplementation Attenuates the Inflammatory Status of Colitis in a Rat Model

Abstract: The aim of this study was to examine the influence of lycopene and beta-carotene on the inflammatory status in a rat model of induced-colitis. Using the 2,4,6-trinitrobenzenesulfonic acid (TNBS) model, colitis was induced in thirty-two male Wistar rats divided into four groups. Each group received a different diet regime in parallel with the induction of colitis and was sacrificed after seven days. The groups were divided as follows: Group A: without colitis and fed a normal chow diet; Group B: induced with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Supporting the results of the present study, lycopene consumption has been shown to have anti-inflammatory properties in a rat model of colitis [42]. Also, the administration of lycopene decreased IL-8 and TNF-α secretion as well as increased the phagocytic activity of pulmonary alveolar macrophages in an LPS-induced lung injury model in rats [43].…”
Section: Discussionsupporting
confidence: 88%
“…Supporting the results of the present study, lycopene consumption has been shown to have anti-inflammatory properties in a rat model of colitis [42]. Also, the administration of lycopene decreased IL-8 and TNF-α secretion as well as increased the phagocytic activity of pulmonary alveolar macrophages in an LPS-induced lung injury model in rats [43].…”
Section: Discussionsupporting
confidence: 88%
“…Cell culture studies also showed that lycopene has antiproliferative and proapoptotic effects on various cancer cell lines [6,7]. Apart from the antioxidant and anticancer effects, lycopene was found to have anti-inflammatory effects in the airway [8,9], prostate [10], and colon [11,12], which are believed to be related to inhibition of the formation of several proinflammatory molecules such as nitric oxide (NO), interleukins, TNF-a, cyclooxygenase, and NF-jB, depending on the cell types and stimuli [13,14]. While the anti-inflammatory effects of lycopene have been indicated in many studies, the mechanisms underlying these effects and the signal transduction pathway affected by lycopene remain elusive.…”
Section: Introductionmentioning
confidence: 98%
“…Among them, lycopene, which can be found in high concentrations in tomatoes [27], has the most potent antioxidant potential [28][29][30]. Lycopene has been shown to decrease inflammation in vivo [31][32][33] and in vitro [33,34]. Of particular interest is the ability of lycopene to reduce airway inflammation, including both neutrophil influx and activation [35].…”
Section: Introductionmentioning
confidence: 99%